"Bits and Pieces" to Improve the Students' Writing Skill: Using Educational Game as an Approach to Teach Descriptive Text - Rizky, Ramanda (Elsya : Journal of English Language Studies, 2020)
Students in Indonesia who learn English as a Foreign Language (EFL) encounter problems in learning how to write in English. Not a novel problem in the least, but the more connected the world is becoming due to the availability of information and communication technologies (ICT). This study aims to address the need to improve the generation’s English skills, lest they are left behind the moving era. This study is a classroom action research (CAR), using a test, observation, field note, and interviews as the research instruments. Twenty-nine middle school students were taught to produce descriptive texts using the approach of an educational game called Bits and Pieces. The results showed that the game improved students’ average scores in writing descriptive text from 70.12 (cycle I) to 79.75 (cycle II) as students’ were unanimously interested in the strategy, much more so than traditional approaches.